Autotrophic denitrification nitrogen removal filler suitable for sewage with low carbon-nitrogen ratio and preparation method of autotrophic denitrification nitrogen removal filler

By using autotrophic denitrification denitrification fillers, the problem of removing nitrate nitrogen in low-carbon nitrogen ratio sewage was solved, and efficient and economical deep denitrification effect was achieved, avoiding the problem of effluent acidification.

CN119874036AActive Publication Date: 2025-04-25HEFEI UNIV OF TECH +1

Patent Information

Application Number
CN202510386376.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-25
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

In the prior art, it is difficult to effectively remove nitrate nitrogen when treating low-carbon nitrogen-specific wastewater, and conventional methods have problems such as high cost, high energy consumption, and acidification of effluent.

Method used

An autotrophic denitrification denitrification filler is used, and its composition includes sulfur aluminate cement, silica fume, modified sodium percarbonate, sulfur powder, pyrite powder and calcium carbonate powder. Through micropore structure and alkalinity regulation, microbial growth and denitrification reaction are promoted.

Benefits of technology

It achieves deep nitrogen removal of low carbon nitrogen than sewage, with a removal rate of up to 90%, avoiding acidification of effluent, and is simple in process and low in cost, making it suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874036A_ABST
    Figure CN119874036A_ABST
Patent Text Reader

Abstract

The invention discloses an autotrophic denitrification nitrogen removal filler suitable for sewage with a low carbon nitrogen ratio and a preparation method thereof. The filler is prepared from the following raw materials in percentage by weight: 40%-45% of sulphoaluminate cement, 8.5% of silica fume, 1.5% of modified sodium percarbonate, 16.8%-25.2% of sulfur powder, 16.8%-25.2% of pyrite powder and 3%-8% of calcium carbonate powder. Experimental results show that the autotrophic denitrification filler provided by the invention has an excellent denitrification effect on a sewage water body with a low carbon-nitrogen ratio, and can meet the technical requirements of deep denitrification treatment. In addition, the autotrophic denitrification nitrogen removal filler provided by the invention is simple in nitrogen removal process, free of fuel melting raw materials, capable of being applied to large-scale production and actual industrial application, rapid in microbial film formation, high in nitrogen removal efficiency, cheap and easily available in raw materials, simple in process and low in requirements on equipment / environment. Therefore, the method has wide development potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of denitrification treatment, and relates to an autotrophic denitrification filler suitable for low carbon-nitrogen ratio sewage and a preparation method thereof. Background Art

[0002] In recent years, with the acceleration of industrialization, a large amount of high-concentration nitrate nitrogen industrial wastewater has been generated. This type of industrial wastewater has very low or even no organic matter content, but contains a high concentration of nitrate nitrogen. Take the steel industry as an example. It is an industrial industry with a large water consumption. The wastewater discharged has the characteristics of low C / N. In addition, other wastewaters with high organic nitrogen concentrations cannot meet the discharge standards after ordinary biochemical treatment. They can only convert organic nitrogen into nitrate nitrogen, and then into high-concentration nitrate nitrogen wastewater, such as chemical wastewater, food wastewater, etc. In addition, the wastewater treatment process of existing sewage treatment plants has certain limitations. Its secondary effluent still contains a certain concentration of total nitrogen, and it basically exists in the form of nitrate nitrogen. The COD in the secondary effluent is generally very low, with low C / N characteristics. With the increase in wastewater discharge, the enhancement of people's environmental awareness and the increasingly stringent requirements of the state on nitrogen discharge of sewage and wastewater, deep denitrification treatment of low C / N wastewater is imperative.

[0003] At present, the methods for removing nitrate nitrogen salts mainly include: physical technology, chemical treatment technology and biological treatment technology. Among them, physical technology includes: adsorption method, ion exchange method and membrane separation method, etc. The adsorption method is to use some materials with large adsorption capacity and specific surface area to adsorb nitrate nitrogen, thereby achieving the removal of nitrate nitrogen. Its advantage is that the principle is simple and only requires the production of materials with large specific surface area, but it is also limited by the high production cost of materials with large adsorption capacity and large specific surface area; the ion exchange method uses the exchange capacity of alkaline anion resin to remove nitrate nitrogen from water by exchanging chloride or carbonate with nitrate nitrogen. This method is simple, efficient, easy to automate, and recyclable, but there is a problem with the treatment of regenerated waste liquid, and it is not suitable for large-scale nitrate nitrogen salt pollution problems; the membrane separation method is to separate the target components by applying a driving force on both sides of the membrane. The membrane separation method mainly includes reverse osmosis and electrodialysis. The reverse osmosis method separates solutes and water through a reverse osmosis membrane, and then relies on external pressure to make water molecules pass through the reverse osmosis membrane to achieve the purpose of separating and removing nitrate nitrogen. This separation technology can concentrate nitrate nitrogen without changing its molecular form, which is convenient for subsequent collection and centralized treatment. Although the reverse osmosis method can concentrate nitrate nitrogen in water, the concentrated liquid needs to be treated secondary, which increases the treatment cost and energy consumption. At the same time, the reverse osmosis process will also remove ions in the water that are beneficial to the human body; the electrodialysis membrane method uses a selective ion exchange membrane as a medium. Under the action of a DC electric field, the nitrate nitrogen salt passes through the membrane and is separated from the water and enters the high-concentration salt water side. The difference in ion concentrations between the light and concentrated chambers increases to achieve the purpose of separation. The electrodialysis membrane method has a high removal efficiency, but the concentrated liquid needs to be further processed, which results in certain limitations in the application of this method.

[0004] Chemical treatment technology: using active metals or catalysts to reduce nitrate nitrogen salts. The chemical reduction method is highly efficient, but it is easy to produce by-products, causing secondary pollution. Although the above physical and chemical technologies react quickly, they have high costs, high energy consumption, and produce concentrated liquid and secondary pollution, which are not suitable for large-scale application.

[0005] Biological treatment technology: Utilizes the denitrification of microorganisms to remove nitrate nitrogen pollution. It can be divided into heterotrophic denitrification and autotrophic denitrification according to the required electron donor. Heterotrophic denitrification technology uses organic carbon sources as electron donors, such as glucose or sodium acetate, and has a fast reaction rate, but is prone to problems such as unstable dosage causing secondary pollution of effluent. The most commonly used autotrophic denitrification technology is sulfur autotrophic denitrification technology, which uses sulfur or sulfur-containing compounds as electron donors and uses sulfur autotrophic denitrifying bacteria to reduce nitrate nitrogen to nitrogen gas for removal. Although sulfur autotrophic denitrification technology does not require an external carbon source and is suitable for denitrification of low C / N wastewater, it will cause effluent acidification and an increase in sulfate concentration; furthermore, when sulfur is used for sulfur autotrophic denitrification denitrification, the fine particles of sulfur used are likely to cause impurities in the effluent, requiring multiple filtrations. In order to solve this problem, the sulfur autotrophic biological filler is currently melted and cooled to make granular filler to prevent the sulfur from flowing away with the effluent. However, it will still cause the effluent to become acidic, and the implementation of the melting and heating process will undoubtedly increase the production cost of the filler, resulting in a higher price.

[0006] In view of this, it is necessary to develop a solid filler that does not require an external carbon source, is low in cost, can prevent the effluent from being too acidic, and is suitable for microbial autotrophic denitrification. Summary of the invention

[0007] In view of the technical problems existing in the background technology, the purpose of the present invention is to provide an autotrophic denitrification filler suitable for low carbon-nitrogen ratio sewage and a preparation method thereof.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions: The first aspect of the present invention provides an autotrophic denitrification filler suitable for low carbon-nitrogen ratio sewage, which includes the following raw materials by weight percentage: 40% to 45% sulphoaluminate cement, 8.5% silica fume, 1.5% modified sodium percarbonate, 16.8% to 25.2% sulfur powder, 16.8% to 25.2% pyrite powder, and 3% to 8% calcium carbonate powder.

[0009] Preferably, the purity of the sulfur powder is 95-99%, the purity of the pyrite powder is above 85%, and the active oxygen content in the modified sodium percarbonate is 13-14%.

[0010] Preferably, the preparation method of the modified sodium percarbonate comprises the following steps: Sodium percarbonate is ground into powder and then passed through a 120-mesh sieve to obtain sodium percarbonate powder with a particle size of 120 meshes; gelatinized starch is ground into powder and then passed through a 120-mesh sieve to obtain gelatinized starch powder with a particle size of 120 meshes; manganese dioxide is ground into powder and then passed through a 120-mesh sieve to obtain manganese dioxide with a particle size of 120 meshes; The processed sodium percarbonate, gelatinized starch and manganese dioxide powder are uniformly mixed and stored at a mass ratio of 7:2:1 to obtain modified sodium percarbonate.

[0011] The particle sizes of the silica fume, sulfur powder, pyrite powder and calcium carbonate powder are all controlled within the range of 80 to 120 meshes.

[0012] The second aspect of the present invention provides a method for preparing the above-mentioned autotrophic denitrification denitrification filler suitable for low carbon-nitrogen ratio sewage, comprising the following steps: S1. Fully mix the raw materials according to the formula to obtain a mixed powder; S2, adding water to the mixed powder, stirring evenly to obtain a slurry; S3. The slurry is made into particles, and the particles are placed in a ventilated place to dry naturally. After the particles are dried naturally, water is sprayed for curing to further solidify the solid particle material to obtain an autotrophic denitrification filler.

[0013] Preferably, the amount of water added is 20-30 wt % of the total mass of the mixed powder.

[0014] Preferably, the particle size of the particles after natural air drying is 5-8 mm.

[0015] Preferably, the natural air drying time is 20 to 24 hours.

[0016] Preferably, the water spraying curing treatment is: use a watering can to spray water on the surface of the particles, wait for them to dry naturally, and repeat this operation for 3 consecutive days, once a day.

[0017] The present invention has the following beneficial effects: (1) The autotrophic denitrification denitrification filler provided by the present invention, wherein sulphoaluminate cement is selected as a binder to ensure the physical strength of the filler, and at the same time, its internal alkalinity after coagulation is lower than that of silicate cement, so that microorganisms are more likely to grow on the filler, and modified sodium percarbonate is used as a foaming agent, and gas is only generated when water is added, which is not easy to waste the gas generated by the foaming agent. With the help of the generated gas, micropores are formed inside the filler, making it easier for microorganisms to grow on the filler, and adding an appropriate amount of calcium carbonate can provide alkalinity to ensure that the effluent after sulfur autotrophic denitrification will not be overly acidified, and pyrite and sulfur are used as sulfur sources. Through the proportion of deployment, sulfur autotrophic denitrification microorganisms can grow rapidly to start the denitrification reaction, while avoiding the acidification of the effluent caused by a single sulfur source. The experimental results show that the autotrophic denitrification filler has an excellent denitrification effect on low-concentration nitrate water bodies and can meet the technical requirements of deep denitrification treatment.

[0018] (2) The actual active oxygen content of the modified sodium percarbonate in the present invention is 13-14%. When the gelatinized starch is mixed with the modified sodium percarbonate to prepare the denitrification filler particles, it can form a highly viscous substance to slow down the rapid impact of oxygen generated by sodium percarbonate when it meets water on the inside of the particles, which affects the particle strength. Manganese dioxide acts as a catalyst for the release of oxygen from sodium percarbonate, ensuring that the oxygen contained in the sodium percarbonate can be completely released before the denitrification filler particles solidify their own strength.

[0019] (3) The autotrophic denitrification filler provided by the present invention can simultaneously provide electron donor sulfur and alkalinity adjustment buffer in the autotrophic microbial denitrification process. The denitrification process is simple and does not require the use of fuel molten raw materials (molten sulfur). It can be applied to large-scale production and actual industrial applications. Microbial biofilm formation is fast, the denitrification efficiency is high, the raw materials are cheap and easy to obtain, the process is simple and has low requirements for equipment / environment, thus saving energy and reducing costs.

[0020] (4) The preparation process of the autotrophic denitrification filler provided by the present invention is simple, and the obtained material structure is stable, which makes it possible to balance the production process and product structure according to different water quality and usage time requirements, greatly increasing the scope of application of the product and facilitating industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 This is an optical picture of the autotrophic denitrification denitrification filler prepared in Example 1; Figure 2 A curve diagram showing the change of nitrate nitrogen concentration with the number of circulating water changes in the denitrification performance test of the autotrophic denitrification filler prepared in Example 1; Figure 3 The graph is a graph showing the change of pH value with the number of water changes during the denitrification performance test of the autotrophic denitrification filler prepared in Example 1; Figure 4 A curve diagram showing the change of nitrate nitrogen concentration with the number of circulating water changes in the denitrification performance test of the autotrophic denitrification filler prepared in Example 2; Figure 5 The graph is a graph showing the change of pH value with the number of water changes during the denitrification performance test of the autotrophic denitrification filler prepared in Example 2; Figure 6It is a curve diagram showing the change of nitrate nitrogen concentration with the number of circulating water changes in the denitrification performance test of molten sulfur autotrophic denitrification filler; Figure 7 This is a curve diagram showing the change of pH with the number of water changes during the denitrification performance test of the molten sulfur autotrophic denitrification filler; Figure 8 A curve diagram showing the change of nitrate nitrogen concentration with the number of circulating water changes in the denitrification performance test of the autotrophic denitrification filler prepared in Example 3; Fig. 9 The graph is a graph showing the change of pH value with the number of water changes during the denitrification performance test of the autotrophic denitrification filler prepared in Example 3; Fig.10 A curve diagram showing the change of nitrate nitrogen concentration with the number of circulating water changes in the denitrification performance test of the autotrophic denitrification filler prepared in Comparative Example 1; Fig.11 The graph is a graph showing the change of pH with the number of circulating water changes in the denitrification performance test of the autotrophic denitrification filler prepared in Comparative Example 1; Fig.12 A curve diagram showing the change of nitrate nitrogen concentration with the number of circulating water changes in the denitrification performance test of the autotrophic denitrification filler prepared in Comparative Example 2; Fig.13 The graph is a graph showing the change of pH with the number of circulating water changes in the denitrification performance test of the autotrophic denitrification filler prepared in Comparative Example 2; Fig.14 A curve diagram showing the change of nitrate nitrogen concentration with the number of circulating water changes in the denitrification performance test of the autotrophic denitrification filler prepared in Comparative Example 3; Fig.15 This is a curve chart showing the change of pH with the number of water changes in the denitrification performance test of the autotrophic denitrification filler prepared in Comparative Example 3. DETAILED DESCRIPTION

[0023] In the following description, for the purpose of illustration rather than limitation, specific details such as specific system structures and technologies are provided to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may also be implemented in other embodiments without these specific details.

[0024] The present invention provides an autotrophic denitrification filler suitable for low carbon-nitrogen ratio sewage, and its raw materials include the following components by weight percentage: 40% to 45% sulphoaluminate cement, 8.5% silica fume, 1.5% modified sodium percarbonate, 16.8% to 25.2% sulfur powder, 16.8% to 25.2% pyrite powder, and 3% to 8% calcium carbonate powder. Among them, sulphoaluminate cement is used as a binder, which mainly plays the role of bonding various component materials together; silica fume is used as a physical reinforcing agent, and adding an appropriate amount of silica fume can increase the strength of the filler; modified sodium percarbonate is used as a foaming agent, and the active oxygen content contained in the modified sodium percarbonate is required to be 13 to 14%. The modified sodium percarbonate generates oxygen when it meets water, which can create small holes inside the filler, increase the porosity of the filler, and then increase the specific surface area, so that microorganisms are more likely to grow on the filler. Modified sodium percarbonate will decompose to release oxygen and water, and the final reaction product contains sodium carbonate (Na2CO3). The generated sodium carbonate can provide a certain alkalinity to avoid excessive acidity caused by autotrophic denitrification.

[0025] Sulfur powder and pyrite powder are the main electron donors for sulfur autotrophic denitrification. The purity of sulfur powder is required to be 95-99%, and the purity of iron ore powder is required to be above 85%. Calcium carbonate powder is mainly used to provide alkalinity to avoid excessive acidity caused by autotrophic denitrification.

[0026] The particle sizes of silica fume, sulfur powder, pyrite powder and calcium carbonate powder must be controlled within the range of 80-120 mesh.

[0027] The principle of using the autotrophic denitrification denitrification filler provided by the present invention to remove nitrate nitrogen salts in water by autotrophic microbial denitrification is: using elemental sulfur or pyrite in sulfur-containing substances to carry out autotrophic denitrification, so that nitrates gain electrons and are reduced to nitrogen gas; sulfur autotrophic denitrification will generate hydrogen ions as the reaction proceeds to reduce the pH value of the water quality, and the calcium carbonate in the filler and the sodium carbonate formed by the foaming agent (modified sodium percarbonate) will provide a certain alkalinity, complement each other, and adjust the acid-base balance of the overall system, thereby achieving the effect of efficient denitrification. The chemical reaction formula involved in the whole process is as follows: 55S 0 +20CO2+50NO3 - +38H2O+4NH4 + →4C5H7O2N+55SO4 2- +25N2+64H + (1) or 2FeS2+6NO3 - +4H2O→3N2 +4SO4 2- +2Fe(OH)3 +2H + (2) The sodium carbonate produced by the reaction between calcium carbonate in the filler and modified sodium percarbonate provides alkalinity. The chemical reaction involved is as follows: 2H + +CaCO3=Ca 2+ +CO2+H2O (3) CO3 2- +2H + =H2O+CO2 (4) Preparation Example The preparation method of the modified sodium percarbonate comprises the following steps: Sodium percarbonate is ground into powder and then passed through a 120-mesh sieve to obtain sodium percarbonate powder with a particle size of 120 meshes; gelatinized starch is ground into powder and then passed through a 120-mesh sieve to obtain gelatinized starch powder with a particle size of 120 meshes; manganese dioxide is ground into powder and then passed through a 120-mesh sieve to obtain manganese dioxide with a particle size of 120 meshes; The processed sodium percarbonate, gelatinized starch and manganese dioxide powder are uniformly mixed and stored in a mass ratio of 7:2:1 to obtain modified sodium percarbonate.

[0028] Example 1

[0029] A method for preparing an autotrophic denitrification filler suitable for low carbon-nitrogen ratio sewage, the specific steps are as follows: S1. Weigh sulfur powder (120 mesh) with a purity of 95%, pyrite powder (120 mesh) with a purity of 86%, calcium carbonate powder (120 mesh) with a purity of 99.5%, ordinary grade 42.5 sulphoaluminate cement, silica fume (120 mesh) and modified sodium percarbonate in the preparation example in a weight ratio of 25.2:16.8:3:45:8.5:1.5, with a total weight of 1 kg of each raw material, and then fully mix them, with the standard that the color of each raw material cannot be distinguished, to obtain a mixed powder; S2. Add 20% water (water-cement ratio 0.2) of the mixed powder mass to the obtained mixed powder, stir evenly to obtain a slurry; S3, after the obtained slurry is stabilized for 1 minute, solid particles with a particle size of 5-8 mm are prepared, and then placed in a ventilated place to stand and dry naturally for 24 hours; S4. The naturally air-dried solid particles are subjected to water spraying curing treatment to further solidify. Specifically, water is sprayed on the surface of the solid particles using a spray bottle, and the solid particles are allowed to dry naturally. This operation is repeated for 3 consecutive days, once a day, and the curing is completed to obtain an autotrophic denitrification filler.

[0030] Example 2

[0031] Sulfur powder (120 mesh) with a purity of 95%, pyrite powder (120 mesh) with a purity of 86%, calcium carbonate powder (120 mesh) with a purity of 99.5%, ordinary grade 42.5 sulphoaluminate cement, silica fume (120 mesh) and the modified sodium percarbonate in the preparation example were weighed according to a weight ratio of 25.2:16.8:8:40:8.5:1.5, with a total weight of 1 kg of each raw material, and then fully mixed, with the standard that the color of each raw material cannot be distinguished, to obtain a mixed powder; the remaining steps are the same as in Example 1, to obtain an autotrophic denitrification filler.

[0032] Example 3

[0033] Sulfur powder (120 mesh) with a purity of 95%, pyrite powder (120 mesh) with a purity of 86%, calcium carbonate powder (120 mesh) with a purity of 99.5%, ordinary grade 42.5 sulphoaluminate cement, silica fume (120 mesh) and modified sodium percarbonate in the preparation example were weighed according to a weight ratio of 16.8:25.2:8:40:8.5:1.5, with a total mass of 1 kg of each raw material, and then fully mixed, with the standard that the color of each raw material cannot be distinguished, to obtain a mixed powder; the remaining steps are the same as in Example 1, to obtain an autotrophic denitrification filler.

[0034] Comparative Example 1 Sulfur powder (120 mesh) with a purity of 95%, pyrite powder (120 mesh) with a purity of 86%, calcium carbonate powder (120 mesh) with a purity of 99.5%, ordinary grade 42.5 sulphoaluminate cement, silica fume (120 mesh) and modified sodium percarbonate were weighed according to a weight ratio of 5:37:8:40:8.5:1.5, with a total weight of 1 kg, and then fully mixed, with the standard that the colors of the raw materials could not be distinguished, to obtain a mixed powder; the remaining steps were the same as in Example 1 to obtain an autotrophic denitrification filler.

[0035] Comparative Example 2 Sulfur powder (120 mesh) with a purity of 95%, pyrite powder (120 mesh) with a purity of 86%, calcium carbonate powder (120 mesh) with a purity of 99.5%, ordinary grade 42.5 sulphoaluminate cement, silica fume (120 mesh) and modified sodium percarbonate were weighed in a weight ratio of 37:5:8:40:8.5:1.5, with a total weight of 1 kg, and then fully mixed, with the standard that the colors of the raw materials could not be distinguished, to obtain a mixed powder; the remaining steps were the same as in Example 1 to obtain an autotrophic denitrification filler.

[0036] Comparative Example 3 According to the weight ratio of 25.2:16.8:8:40:8.5:1.5, sulfur powder (120 mesh) with a purity of 95%, pyrite powder (120 mesh) with a purity of 86%, calcium carbonate powder (120 mesh) with a purity of 99.5%, ordinary grade 42.5 sulphoaluminate cement, silica fume (120 mesh) and ordinary commercially available sodium percarbonate were weighed, purchased from McLean Reagent, item number S830224, and its active oxygen content was 13-14%. The total mass of each raw material was 1 kg, and then fully mixed, with the standard that the color of each raw material could not be distinguished, to obtain a mixed powder; the remaining steps were the same as in Example 1 to obtain an autotrophic denitrification filler.

[0037] Experimental study on denitrification performance of autotrophic denitrification filler A certain amount of autotrophic denitrification filler was taken for denitrification experiment, and the denitrification capacity of each filler was analyzed through the experimental results.

[0038] (1) Experimental methods The experimental contents are as follows: The experimental water is simulated secondary effluent, that is, a certain amount of CH3COONa, KNO3 and KH2PO4 are added to the tap water. The water quality characteristics are: pH is controlled at 7.0~7.3, nitrate nitrogen concentration is about 30mg / L, COD concentration is about 45mg / L, total phosphorus is about 3.0mg / L, and COD:TN is 1.5.

[0039] Take 30g of the autotrophic denitrification filler prepared in Examples 1-3 and Comparative Examples 1-2 respectively and put them into a 250mL conical flask as the experimental group. At the same time, put the commercially available molten sulfur autotrophic denitrification filler into a 250mL conical flask as the control group, add 30mL of activated sludge that has been enriched and cultured, and then add experimental water to the mark. After sealing the conical flask, put it in a shaker at 60r / min and shake it. Control the temperature to 30℃±1℃. Control the hydraulic retention time to 4h, change 200mL of water each time and re-add experimental water to the mark. Continuously measure the nitrate nitrogen concentration and pH of the effluent each time the water is changed. The results are shown in the table. Figure 2-13 .

[0040] Depend on Figure 2 The results of the curve of nitrate nitrogen concentration changing with the number of circulating water changes show that the autotrophic denitrification filler prepared in Example 1 has good denitrification performance. After the reaction, the nitrate nitrogen concentration can be reduced to below 3 mg / L, and the removal rate can reach more than 90%.

[0041] Depend on Figure 3From the results of the water exchange cycles and the pH change curve, it can be seen that the effluent pH of the autotrophic denitrification filler prepared in Example 1 gradually stabilized and fluctuated between 6.6 and 6.9 after the eighth water exchange. Compared with the influent, it showed a certain degree of acidification, but it was not lower than 6.5 (when the pH was lower than 6.5, the effluent would be significantly acidified, affecting the denitrification of the autotrophic denitrifying microorganisms).

[0042] Depend on Figure 4 From the curve of the change of nitrate nitrogen concentration with the number of water changes, it can be seen that the autotrophic denitrification filler prepared in Example 2 has good denitrification performance. After the 11th water change, the nitrate nitrogen removal efficiency can reach 93% when the operation is stable, and the nitrate nitrogen concentration can be reduced to below 3 mg / L. After the 7th water change, the autotrophic denitrifying microorganisms have adapted to the reaction conditions and can begin to operate at a higher nitrate nitrogen removal rate.

[0043] Depend on Figure 5 The results of the water exchange cycles and pH curves show that the pH of the effluent from the autotrophic denitrification filler prepared in Example 2 has been stable at around 7, and no obvious acidification has occurred compared to the influent. Compared with Example 1, 8% by mass of calcium carbonate provides sufficient alkalinity.

[0044] Depend on Figure 6 The results show that the nitrate nitrogen removal efficiency of the molten sulfur autotrophic denitrification filler is about 90% when the operation is stable.

[0045] Depend on Figure 7 The results show that as the nitrate nitrogen removal rate of the molten sulfur autotrophic denitrification filler increases, the effluent pH will drop below 6.5. Since the optimal pH range for autotrophic denitrifying microorganisms is 6.5-8, a pH below 6.5 will affect the denitrification of autotrophic denitrifying microorganisms.

[0046] Depend on Figure 4 and Figure 6 The results show that the autotrophic denitrification filler prepared in Example 2 has a higher adaptation rate of denitrifying microorganisms than the molten sulfur autotrophic denitrification filler. This is reflected in that as the number of water changes increases, the rate at which the nitrate nitrogen concentration in the effluent decreases is higher than that in the control group. This indicates that the pores formed in the filler by the gas generated by the modified sodium percarbonate (as a foaming agent) successfully provide attachment points for microorganisms, allowing the microorganisms to adapt faster. At the same time, it is found that the highest denitrification effect of the autotrophic denitrification filler prepared in Example 2 is also higher than that of the molten sulfur autotrophic denitrification filler.

[0047] Depend on Figure 5 and Figure 7The results show that the effluent of the autotrophic denitrification filler prepared in Example 2 is not acidified, while the effluent of the molten sulfur autotrophic denitrification filler is acidified. This is because an appropriate amount of calcium carbonate and modified sodium percarbonate are added to the raw material formula of the autotrophic denitrification filler prepared in Example 2. The sodium carbonate produced by calcium carbonate and modified sodium percarbonate in water provides sufficient alkalinity, thereby preventing the effluent acidification caused by hydrogen ions produced by autotrophic denitrification microorganisms during the denitrification process.

[0048] In summary, the autotrophic denitrification filler prepared in Example 2 can provide a better microbial growth environment and prevent effluent acidification compared with the molten sulfur autotrophic denitrification filler, and the production process is simple and does not require additional energy, so the cost is lower.

[0049] Depend on Figure 8 The results show that the microorganisms of the autotrophic denitrification filler prepared in Example 3 adapt slightly slower, and can only stabilize to a higher nitrate nitrogen removal rate after the 12th and 13th water changes. After stable operation, the nitrate nitrogen concentration of the effluent is basically above 3 mg / L, and the nitrate nitrogen removal rate is about 89% (lower than 90%). The nitrate nitrogen removal rate and microbial adaptation speed are slightly lower than those of the autotrophic denitrification filler prepared in Example 2. The reason is that the proportion of pyrite components in the formula of this embodiment is increased, and the autotrophic denitrification microorganisms need longer time to adapt in the experiment, and thus the time required to achieve a higher nitrate nitrogen removal rate is also longer.

[0050] Depend on Fig. 9 The results show that the pH of the effluent from the autotrophic denitrification filler prepared in Example 3 fluctuates around 7, and no obvious acidification occurs compared to the influent. This is because the calcium carbonate component can ensure sufficient alkalinity supply when the proportion is 8%.

[0051] Depend on Fig.10 From the curve of the change of nitrate nitrogen concentration with the number of water changes, it can be seen that the nitrate nitrogen removal rate of the autotrophic denitrification filler prepared in comparative example 1 is about 86% after the 15th water change, and the nitrate nitrogen removal rate is as high as 89%. The nitrate nitrogen removal rate of the autotrophic denitrification filler prepared in the above embodiment 2 is close to 90% after the 7th water change, and the highest nitrate nitrogen removal rate reaches more than 90%. The reason why more water changes are required to achieve a high removal rate in comparative example 1 and the nitrate nitrogen removal rate decreases is that too much pyrite is used in comparative example 1, resulting in a slow adaptation speed of denitrifying microorganisms. Although pyrite and sulfur are both electron donors for autotrophic denitrifying microorganisms, in actual experiments and applications, sulfur is more easily used by autotrophic denitrifying microorganisms as an electron donor, and the speed of microorganisms' metabolism and reproduction through it as an electron donor is also faster.

[0052] Depend on Fig.11The results of the water exchange cycles and pH curves show that the pH of the effluent from the autotrophic denitrification filler prepared in Comparative Example 1 has been stable and fluctuated around 7, and no obvious acidification has occurred in the influent. This is because in the present invention, calcium carbonate is mainly used to provide alkalinity to prevent the acidification of the effluent caused by hydrogen ions generated by autotrophic denitrification. The calcium carbonate component accounting for 8% can provide sufficient alkalinity and effectively prevent hydrolysis acidification.

[0053] Depend on Fig.12 From the curve of nitrate nitrogen concentration changing with the number of water changes, it can be seen that the autotrophic denitrification filler prepared in Comparative Example 2 has good denitrification performance, and the autotrophic denitrification microorganisms adapt quickly. The removal rate reached 87% at the 8th water change; at the 9th water change, the nitrate nitrogen removal rate was above 90%, and the nitrate nitrogen concentration could be reduced to below 3 mg / L. Compared with the autotrophic denitrification filler prepared in Comparative Example 1, the autotrophic denitrification microorganisms prepared in Comparative Example 2 adapted much faster, which is consistent with the fact that sulfur is easier to be used by autotrophic denitrification microorganisms as an electron donor. After the 9th water change, the nitrate nitrogen removal effect fluctuated significantly. Combined with the number of water changes and the pH change curve (see Fig.13 ), after the 9th water change, the pH fluctuated significantly, with the highest at 6.94 and the lowest at 6.49. When the pH was lower than 6.5, the effluent was significantly acidified, which affected the denitrification of autotrophic denitrifying microorganisms and reduced the denitrification efficiency, which led to the subsequent fluctuation of nitrate nitrogen in the effluent. The above results show that if the amount of sulfur component is too much, it will cause the effluent to be severely acidified and the pH will be reduced, and even affect the denitrification effect.

[0054] In addition, it should be emphasized here that compared with pyrite, the sulfur used in the present invention produces much more hydrogen ions than pyrite in the denitrification principle when removing the same concentration of nitrate nitrogen. The acidity generated is higher when the sulfur content is very high. The use of only 8% calcium carbonate in Comparative Example 2 cannot provide sufficient alkalinity.

[0055] Compared with Example 2, the removal rate of nitrate nitrogen of the autotrophic denitrification filler prepared in Comparative Example 2 is close to that of Example 2, and the adaptation speed of the autotrophic denitrification microorganisms is also comparable. However, since the calcium carbonate used in Comparative Example 2 cannot provide sufficient alkalinity, the pH of the effluent of Comparative Example 2 decreases more significantly.

[0056] Depend on Fig.14 From the curve of nitrate nitrogen concentration changing with the number of water changes, it can be seen that the autotrophic denitrification filler prepared in comparative example 3 has good denitrification performance. After the 10th water change, the nitrate nitrogen removal efficiency can reach 91.5% when the operation is stable, and the nitrate nitrogen concentration can be reduced to below 3 mg / L.

[0057] The overall removal rate of Example 2 is lower, and Example 2 achieved a removal rate of more than 92.5% in the 8th water change. And the slope of the effluent nitrate nitrogen concentration curve is smaller than that of Example 2, which reflects that the adaptation of the autotrophic denitrification filler microorganisms in Comparative Example 3 takes longer. At a deeper level, it reflects that the modified sodium percarbonate uses manganese dioxide to release oxygen in time to produce micropores before the filler solidifies. At the same time, the gelatinized starch slows down the impact on the inside of the particles, making the micropores uniform and providing more attachment space for microorganisms. However, traditional sodium percarbonate is not as good as the autotrophic denitrification filler in Example 2 in terms of the number and volume of micropores due to its slow release and sometimes fast and sometimes slow release. The higher effluent nitrate nitrogen and fluctuating concentration reflect that the upper limit of the micropore volume of the filler in Comparative Example 3 is insufficient, and some microorganisms are lost with the water change.

[0058] Depend on Fig.15 The results of the water exchange cycles and pH curves show that the pH of the effluent in Comparative Example 3 fluctuates around 7, and drops to 6.79 at its lowest, without significant acidification. Basically the same as Example 2, in the case of insufficient micropores inside the filler in Comparative Example 3, the number of autotrophic denitrifying microorganisms is less than that in Example 2, and the added calcium carbonate is sufficient to provide alkalinity.

[0059] The present invention is not limited to the above-mentioned specific implementation modes. Various changes made by ordinary technicians in this field based on the above-mentioned concepts without creative work are all within the protection scope of the present invention.

Claims

1. An autotrophic denitrification filler suitable for low carbon-nitrogen ratio sewage, characterized in that: The raw materials include the following by weight percentage: 40% to 45% sulphoaluminate cement, 8.5% silica fume, 1.5% modified sodium percarbonate, 16.8% to 25.2% sulfur powder, 16.8% to 25.2% pyrite powder, and 3% to 8% calcium carbonate powder.

2. The autotrophic denitrification filler suitable for low carbon-nitrogen ratio sewage according to claim 1, characterized in that: The purity of the sulfur powder is 95-99%, the purity of the pyrite powder is above 85%, and the active oxygen content in the modified sodium percarbonate is 13-14%.

3. The autotrophic denitrification and denitrification filler suitable for low carbon-nitrogen ratio sewage according to claim 1, characterized in that: The preparation method of the modified sodium percarbonate comprises the following steps: Sodium percarbonate is ground into powder and then passed through a 120-mesh sieve to obtain sodium percarbonate powder with a particle size of 120 meshes; gelatinized starch is ground into powder and then passed through a 120-mesh sieve to obtain gelatinized starch powder with a particle size of 120 meshes; manganese dioxide is ground into powder and then passed through a 120-mesh sieve to obtain manganese dioxide with a particle size of 120 meshes; The processed sodium percarbonate, gelatinized starch and manganese dioxide powder are uniformly mixed and stored in a mass ratio of 7:2:1 to obtain modified sodium percarbonate.

4. The autotrophic denitrification filler suitable for low carbon-nitrogen ratio sewage according to claim 1, characterized in that: The particle sizes of the silica fume, sulfur powder, pyrite powder and calcium carbonate powder are all controlled within the range of 80 to 120 meshes.

5. A method for preparing an autotrophic denitrification filler suitable for low carbon-nitrogen ratio sewage as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Fully mix the raw materials according to the weight percentage to obtain a mixed powder; S2, adding water to the mixed powder, stirring evenly to obtain a slurry; S3. The slurry is made into particles, and the particles are placed in a ventilated place to dry naturally. After the particles are dried naturally, water is sprayed for curing to further solidify the solid particle material to obtain an autotrophic denitrification filler.

6. The method for preparing the autotrophic denitrification denitrification filler suitable for low carbon-nitrogen ratio sewage according to claim 5, characterized in that: The amount of water added is 20-30wt% of the total mass of the mixed powder.

7. The method for preparing the autotrophic denitrification denitrification filler suitable for low carbon-nitrogen ratio sewage according to claim 5, characterized in that: The particle size of the particles after natural air drying is 5~8mm.

8. The method for preparing the autotrophic denitrification denitrification filler suitable for low carbon-nitrogen ratio sewage according to claim 5, characterized in that: The natural air drying time is 20 to 24 hours; the water spray curing treatment is: use a spray bottle to spray water on the surface of the particles, wait for them to dry naturally, and repeat this operation for 3 consecutive days, once a day.

Citation Information

Patent Citations

  • Adsorption material for phosphorus and heavy metal polluted water and preparation method thereof

    CN107790099A

  • Method for removing metal thallium in wastewater

    CN109437386A

  • Material for nitrogen removal by autotrophic denitrification method as well as preparation method and application of material

    CN115259372A

  • Autotrophic denitrification nitrogen removal composite filler as well as preparation method and application thereof

    CN117466433A

  • Starch-based sodium percarbonate green oxygen release agent as well as preparation method and application thereof

    CN119563704A

Cited By

  • Sulfur-iron coupling filter material as well as preparation method and application thereof

    CN122426865A

  • Sulfur-iron coupled filter material, method of making and use thereof

    CN122426865B